Faktor-faktor yang mempengaruhi struktur modal pada perusahaan farmasi yang terdaftar di BEI periode 2015-2020 - Kristina , Desi; Jumono, Sapto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of Net Profit Margin, Current ratio , Growth Asset, Firm Size Sales, Assset Structure, and covid-19 condition (dummy) on the Capital Structure (Long Term Debt Equity) in manufacturing companies in the pharmaceutical sub-sector on the IDX for the 2015-2020 period. Using a sampling technique with purposive sampling and obtained 8 issuers with a research period of 6 years (quarters), and the total sample data is 192. The method of analysis in this study is panel data regression. The results of this study indicate that simultaneously the NPM, CR, GA, FZS, AS, and Dummy influence the long-term debt equity (LTDER). Result from GA, AS, and Dummy partially have a significant positive effect on long-term debt equity. While the NPM, CR, and FZS partially have a significant negative influence on long-term debt equity.